Manipulative Messages in 'Ice Cold: Murder, Coffee, and Jessica Wongso': A Case Study of a Netflix Documentary - Muhammad Qadaruddin; Nining Artianasari; Fikruzzaman Saleh; Jalihah Md Shah (FAKULTAS DAKWAH UIN SALATIGA, 2024)
This research examines the presence and implications of manipulative messages in the Netflix documentary